The Future of Public Relations, Advertising and Journalism: How Artificial Intelligence May Transform the Communication Profession and Why Society Should Care? - Nilüfer Türksoy (Türkiye İletişim Araştırmaları Dergisi)
This study aims to examine the latest academic research conducted in the last decade on the future benefits, challenges, and impact of Artificial Intelligence and its adoption in the communication profession. The study is grounded in the perceptions of reviews from relevant academic articles and emphasizes the technological innovations related to Artificial Intelligence applications within the public relations, advertising, and journalism professions. The followings are some of the key questions asked in the current study: 1) How is the implementation of Artificial Intelligence going to impact the jobs of the communication profession? 2) Can robots replace public relations, advertising, and journalism professionals? and 3) What kind of opportunities and challenges will AI-powered systems bring to these three professions? The findings suggest that Artificial Intelligence would benefit the communication profession and those who adopt Artificial Intelligence technologies would certainly gain a competitive advantage. It appears that the future of the communication profession would be a blend of both Artificial Intelligence technologies and human insight. Also, it is emphasized that it would be a rather narrow view to see that Artificial Intelligence would create robots to replace humans while performing various tasks or would outperform human intelligence in most of its dimensions.